Experimental and numerical study on steel wire mesh reinforced concrete slab under contact explosion - Li, J.; Wu, C.; Hao, Hong; Su, Y. (Elsevier, 2017)
With the rising of terrorism and rapid urbanization around the world, increasingly more structures are exposed to the threats from accidental and hostile explosion loads. To provide adequate structural protection against blast load, novel materials and strengthening techniques are under fast development. In the present study, a composite slab design aiming at high level blast resistance is studied. In the matrix of high strength self-compacting concrete, besides conventional rebars serving as primary reinforcement, steel wire meshes are embedded and served as secondary reinforcements. Moreover, on the concrete cover layer where the tensile cracks locate, steel fibres are added to provide micro crack-bridging effect. Preliminary numerical simulations adopting coupled Finite Element (FE) and Smoothed Particle Hydrodynamics (SPH) are carried out in hydro-code and the results are used as guide for field blast test. Composite slab with optimal design is field tested under 1 kg TNT contact detonation, and the results are compared with slabs made of conventional and ultra-high performance concrete without steel wire meshes. The results demonstrate that slab with steel wire mesh reinforcement develops localized membrane effect when subjected to blast loads and shows better blast resistant capability as compared to the slabs without steel wire meshes.